The Polarization and Impedance Controlled Car: An Interactive Tool for Teaching Electromagnetic Principles - Teo Bergkvist; Otto Edgren; Oscar Gren; Mans Jacobsson; Christian Nelson; Johan Lundgren (IEEE Access)
The Polarization and Impedance Controlled Car (PICC) presents an innovative approach for demonstrating and teaching key principles of electromagnetic field theory, specifically polarization and impedance. Designed as an interactive learning tool, the PICC utilizes a radio-controlled car, NanoVNA, Raspberry Pi, and handheld antennas to visualize real-time effects of polarization and impedance. The system incorporates two orthogonal linearly polarized patch antennas on a shared ground plane connected to a NanoVNA. A strip grid is utilized to affect the reflection and transmission properties of the two antennas, which in turn enables controlled car movements. This paper details the design, measurements, and simulations involved in creating the PICC and introduces an open-source Python library for NanoVNA data streaming. The PICC illustrates a practical application of electromagnetic principles potentially providing a more engaging learning experience for undergraduate students.